Perancangan Mesin Pemipil Jagung Dengan Poros Gerigi Berpenggerak Gasoline Engine - Alif Imam Utomo; Iwan Nugraha Gusniar; Eka Yulianty (Politeknik Negeri Padang, 2023)
Corn is the main food after rice, corn has the same nutritional value of protein, carbohydrates, and calories as rice. In everyday life, corn, in addition to being used as a food ingredient, can also be used as an industrial raw material and animal feed. But in the processing process, there are still difficulties if done manually because it takes a long time to shell corn kernels before being processed into corn-based foods. Therefore, a tool is needed to support the availability of corn quickly and support corn productivity. So, the author designed a corn sheller machine that can increase time efficiency. From the results of the design of the components used in the corn sheller machine, the diameter of the shaft used was at least 28 mm, the v-belt used was typed A with a length of 40 inches totaling 2 pieces, a drive pulley with a diameter of 2 inches, a pulley that was driven by 6 inches in diameter, the key used were 8mm x 7mm x 18mm, and used a gasoline engine with a power of 5.5 Hp. After the shelling test obtained capacity 360 kg per hour.